Arctic art education in changing nature and culture - Timo Jokela; Maria Huhmarniemi (University of Aberdeen, School of Education, 2022)
The interconnection between the ecological and the cultural is evident in the Arctic. Thus, we propose the term ecoculture to highlight the connection of communities to places. Ecological knowledge, Indigenous knowledge, tacit knowledge and local knowledge are some of the concepts that highlight diverse ways of knowing in rural communities living close to nature. We use the terms northern knowledge, Arctic art education and new genre Arctic art, to discuss how art in North and the Arctic can foster education for sustainability and revitalisation of ecoculture. The long-term art-based action research to develop Arctic art education at winter circumstances is presented in this article. The research has included a number of winter art projects in Northern Scandinavia and North-West Russia. Three winter art projects, carried out in remote villages together with communities and schools, are reflected and theorized in this article. Artists, teachers and participants of winter art projects have transformed northern knowledge to respond to needs of contemporary society. As a result of the action research, wintery ecoculture has been revitalized and knowing with nature has been fostered as response to decolonisation needs. Research shows that new genre Arctic art and Arctic art education can revitalise ecoculture and northern knowledge.